The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1743-422x-8-136
|View full text |Cite
|
Sign up to set email alerts
|

The full genome sequence of three strains of Jamestown Canyon virus and their pathogenesis in mice or monkeys

Abstract: BackgroundJamestown Canyon virus (JCV), family Bunyaviridae, is a mosquito-borne pathogen endemic in the United States and Canada that can cause encephalitis in humans and is considered an emerging threat to public health. The virus is genetically similar to Inkoo virus circulating in Europe, suggesting that much of the northern hemisphere contains JCV or similar variants.ResultsWe have completed the sequence of three isolates of JCV collected in geographically diverse locations over a 57 year time span. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
(36 reference statements)
4
15
0
Order By: Relevance
“…Similarly, we did not detect JCV by RNA sequencing from acute serum and CSF from a third patient (Piantadosi et al, in preparation). While these were residual samples that may have been degraded by freeze/thaw cycles, our findings are consistent with prior results; JCV has never been isolated from human samples, and one study demonstrated no detectable viremia in experimentally infected rhesus macaques, despite seroconversion [34]. In general for orthobunyaviruses, it has been challenging to grow virus [35] or detect viral RNA in human samples; the few exceptions to this have included the detection of RNA from LACV in brain tissue [36], Oropouche virus in leukocytes [37], and Cache Valley virus in the CSF of an immunocompromised patient [38].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, we did not detect JCV by RNA sequencing from acute serum and CSF from a third patient (Piantadosi et al, in preparation). While these were residual samples that may have been degraded by freeze/thaw cycles, our findings are consistent with prior results; JCV has never been isolated from human samples, and one study demonstrated no detectable viremia in experimentally infected rhesus macaques, despite seroconversion [34]. In general for orthobunyaviruses, it has been challenging to grow virus [35] or detect viral RNA in human samples; the few exceptions to this have included the detection of RNA from LACV in brain tissue [36], Oropouche virus in leukocytes [37], and Cache Valley virus in the CSF of an immunocompromised patient [38].…”
Section: Discussionsupporting
confidence: 91%
“…We have previously demonstrated that JCV infection generates a neutralizing antibody response that also efficiently neutralizes both LACV and TAHV viruses (3,4). In the current study, we found that immunization with rJCV/LACV protected mice against lethal challenge with JCV, LACV, or TAHV.…”
Section: Discussionsupporting
confidence: 58%
“…JCV used in this study was a biological clone of the prototype strain 61V2235 (JCV/61/CO-cl) and previously sequenced and characterized (4). The recombinant LACV (rLACV) was generated from cDNA sequence of LACV strain 78 V 13193 (LACV/78/NC-cl) and was previously sequenced and characterized (5).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Interestingly, similar patterns of pathogenicity are observed in weanling mice inoculated with the CSG viruses known to cause human disease. Weanling mice are susceptible to disease from CEV, JCV, and INKV following IC or IN inoculation, but not following IP inoculation, indicating these viruses are neurovirulent, but not neuroinvasive, in mice [3,21,165]. LACV, SSHV, and TAHV all cause neuroinvasive disease in weanling mice following IP inoculation.…”
Section: Neuropathogenesis – Experimental Infections Of Animalsmentioning
confidence: 99%
“…In experimental infections of rhesus monkeys inoculated subcutaneously or intramuscularly with LACV, TAHV, or JCV, none of the monkeys developed disease [125,165,168]. However, nearly all monkeys developed high neutralizing antibody titers, indicating they were productively infected [125,165,168].…”
Section: Neuropathogenesis – Experimental Infections Of Animalsmentioning
confidence: 99%